The Role of Integrated Marketing Communication (IMC), on Purchase Decision Through Customer Experience in Housing PT. Grand Zamzam Indonesia - Ma'ruf Nidhomuddin; David Sukardi Kodrat (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
Housing is one of society's essential needs, and PT. Grand Zamzam Indonesia is a property developer in Lumajang. Due to the rapid competition in the housing market, Integrated Marketing Communication (IMC) is crucial to provide the right customer experience and maximize purchasing decisions. The questionnaire was distributed directly to customers (buyers) of PT. Grand Zamzam Indonesia, with a total of 129 respondents. The data analysis was conducted using Smart PLS software version 3.0. Based on the results of data processing, the researcher draws the following conclusions: the effect of IMC on purchasing decisions through customer experience is higher, with a coefficient (O) of 0.342, compared to the direct effect of IMC on purchasing decisions, with a coefficient (O) of 0.266. Briefly, the researcher suggests the following recommendations based on the study findings: 1) For the IMC variable, the researcher recommends modifying the lowest mean of X2.1 (information via Tik Tok) with a mean of 3.42. The highest mean at X3.1 (meeting directly with marketing in the marketing office) with a mean of 4.12 should be maintained; 2) Regarding the customer experience variable, the company is advised to develop new strategies for the lowest mean of Y2.2 (freelance marketing recommendations) with a mean of 3.56. The highest means at Y1.1 (selection of house type) and Y1.2 (reputation brand) with means of 4.22 should be maintained with more innovative approaches.